Insomnia - King, Stephen (London New English Library, 1994)
Ralph's insomnia gets worse when Ed Deepneau gets out of control. Ed is obsessed with the notion that Derry is becoming the new Armageddon and that time is ticking away for the residents. An evil of imaginable proportions has began and Ralph has one chance to beat it.
English Fiction.
Keywords: Insomnia -- Maine -- Horror tales